2014
DOI: 10.1073/pnas.1417508112
|View full text |Cite
|
Sign up to set email alerts
|

A red meat-derived glycan promotes inflammation and cancer progression

Abstract: A well known, epidemiologically reproducible risk factor for human carcinomas is the long-term consumption of "red meat" of mammalian origin. Although multiple theories have attempted to explain this human-specific association, none have been conclusively proven. We used an improved method to survey common foods for free and glycosidically bound forms of the nonhuman sialic acid N-glycolylneuraminic acid (Neu5Gc), showing that it is highly and selectively enriched in red meat. The bound form of Neu5Gc is bioav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
332
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 345 publications
(346 citation statements)
references
References 49 publications
9
332
1
4
Order By: Relevance
“…In addition, as elicited anti-Neu5Gc antibodies recognize different patterns of Neu5Gc epitopes than "natural" ones (26) and their presence results in increased long-term exposure of Neu5Gc-positive ECs to these antibodies, they may trigger a chronic inflammation of graft vascular walls, as further discussed below. Indeed, in Cmah KO mice, an animal model unable to biosynthesize Neu5Gc, similarly to humans, it has been demonstrated that anti-Neu5Gc antibodies can stimulate chronic inflammation in dietary Neu5Gc-charged tissues (36). A number of types of antibody specificities against rabbit IgG were explored.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as elicited anti-Neu5Gc antibodies recognize different patterns of Neu5Gc epitopes than "natural" ones (26) and their presence results in increased long-term exposure of Neu5Gc-positive ECs to these antibodies, they may trigger a chronic inflammation of graft vascular walls, as further discussed below. Indeed, in Cmah KO mice, an animal model unable to biosynthesize Neu5Gc, similarly to humans, it has been demonstrated that anti-Neu5Gc antibodies can stimulate chronic inflammation in dietary Neu5Gc-charged tissues (36). A number of types of antibody specificities against rabbit IgG were explored.…”
Section: Discussionmentioning
confidence: 99%
“…There is also experimental evidence for Neu5Gc acting as a xeno-auto antigen capable of exacerbating an inflammatory reaction within vasculature endothelium [15]. A recent study proved that the dietary xenoglycan Neu5Gc causes increased cancer via systemic inflammation in a mouse model [16]. More sensitive detection methods have provided evidence for widespread anti-Neu5Gc antibodies in most humans tested, including IgM, IgA, and IgG antibodies [17].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Neu5Gc-containing glycoconjugates are hydrolyzed to Neu5Gc monosaccharides in lysosomes. Neu5Gc monosaccharides are transported to cytosol, and Neu5Gc is activated to CMP-Neu5Gc by CMP-sialic acid synthetase in the nucleus (21)(22)(23). (ii) In the de novo synthesis pathway, sialic acid Neu5Ac is synthesized in cytosol and activated to CMPNeu5Ac in the nucleus, and CMP-Neu5Ac is subsequently converted to CMP-Neu5Gc by the enzyme CMP-Neu5Ac hydroxylase (CMAH) in cytosol (24,25).…”
Section: Changes Of Sialic Acid Species In Gangliosides During Myogenmentioning
confidence: 99%